Bioaccumulation some heavy metals in the muscle two species of fish in the Konarak and Pozm fishing ports - Ahmad Khoshbin; Alireza Pourkhabbaz (Mashhad University of Medical Sciences, 2021)
Background & objectives: One of the major global concerns about the environment is the pollution of aquatic ecosystems by heavy metals. These elements contaminate aquatic environments and accumulate and concentrate through bioaccumulation in the tissues of living organisms at higher levels of the food chain consumed by humans. In this study, the concentrations of three heavy metals, lead, nickel and cadmium, in the muscle tissue of two species of fish Otolithes ruber and Sphyraena forsteri in the fishing ports of Konarak and Pozm were investigated. Material & Methods: 36 fish samples were collected from Konarak and Pazm ports. After preparation of the samples by acid digestion, the concentrations of heavy elements lead, nickel and cadmium were measured by Contr-AA-700 atomic absorption spectrometer. Data were analyzed using SPSS software (version 20) and ANCOVA and Pearson correlation tests at a significance level of 0.05%. Results: According to the results of the study, there was no significant difference between the amounts of lead, nickel and cadmium in the muscle tissue of Otolithes ruber and Sphyraena forsteri (P> 0.05). The average concentrations of heavy metals lead, cadmium, and nickel in the muscle of fish caught from Konarak port were higher than the samples of Pozm Bay. Also, the concentrations of heavy metals lead, nickel and cadmium in Sphyraena forsteri fish were lower than those of Otolithes ruber samples. Conclusion: The results of the present study showed that the levels of lead and cadmium in the muscle tissue of the studied fish were lower than the standards of the US Food and Drug Administration, the UK Department of Fisheries and Agriculture, the World Food and Agriculture Organization and the US Environmental Protection Agency. The concentration of nickel in the muscle of the studied fish was higher than the permissible limit of the World Health Organization.